Valorizing Rice Straw and Its Anaerobically Digested Residues for Biochar to Remove Pb(II) from Aqueous Solution - Jinyang Li; Fei Shen; Gang Yang; Yanzong Zhang; Shihuai Deng; Jing Zhang; Yongmei Zeng; Tao Luo; Zili Mei (International Journal of Polymer Science)
To seek a new path to valorize rice straw (RS) and its anaerobically digested residues (DRS), biochar production at different temperatures for removing Pb(II) from aqueous solution and its basic physicochemical characteristics for elucidating potentially adsorption mechanisms were investigated. Overall, pH, electrical conductivity (EC), ash, specific surface area (SA), micronutrient content, and aromaticity of RS biochars (RSBCs) and DRS biochars (DRSBCs) increased with the promoted pyrolysis temperature, and opposite trends were found on the yield, volatile matter, H, N, and O. Lower pH and K content but higher yield, carbon stability, and N and P content were achieved by DRSBCs. Consequently, DRSBCs exhibited lower Pb(II) removal, which was 0.15–0.35 of RSBCs. Maximum adsorption capacities of 276.3 and 90.5 mg·g−1 were achieved by RSBC and DRSBC, respectively, at 500°C. However, distinct mechanisms dominated Pb(II) removal, in which carbonates and carboxylates were responsible for RSBCs, and phosphate silicate precipitation and complexation with carboxylate groups controlled DRSBCs.